Organic Fertilizer Purchasing Behavior of Vegetable Farmers in Ngablak Sub-District, Magelang District: Extended Theory of Planned Behavior Approach - Anggiana Shifwah Johar; Hani Perwitasari; Lestari Rahayu Waluyati (Faculty of Animal and Agricultural Science, Diponegoro University, 2026)
In an effort to develop organic farming in Magelang, especially in Ngablak Subdistrict, a thorough and comprehensive understanding of farmers' purchasing behavior regarding organic fertilizer products is essential. This study aims to (1) Examine how attitude, subjective norm, perceived behavioral control, and environmental concern impact the vegetable farmers in Ngablak District intention to purchase organic fertilizer; (2) assess the extent to which purchase intention affects vegetable farmers behavior in purchasing organic fertilizer; and (3) Investigate the role of trust and price consciousness as moderating variables in the relationship among purchasing intention and purchasing behavior of organic fertilizer. This research involved a sample of 123 vegetable farmers in Ngablak sub-district, Magelang district. SEM-PLS method is employed to analyze the data. Empirical findings reveal that attitudes, subjective norms, perceived behavioral control, and environmental concerns significantly and positively contribute to the purchasing intention of organic fertilizer. Futhermore, purchasing intention plays a significant and positive role in shaping the purchasing behavior of organic fertilizer. The association among purchasing intention and purchasing behavior of organic fertilizer is positively moderated by trust. Meanwhile, the moderating role of price consciousness in the relationship between organic fertilizers purchasing intention and purchasing behavior is found to be insignifican.